Endemic trees in a tropical biodiversity hotspot imperilled by an invasive tree. (January 2018) - Bellingham, Peter J.; Tanner, Edmund V.J.; Martin, Patrick H.; Healey, John R.; Burge, Olivia R.
Abstract: Non-native plants invade some tropical forests but there are few long-term studies of these invasions, and the consequences for plant richness and diversity are unclear. Repeated measurements of permanent plots in tropical montane rain forests in the Blue and John Crow Mountains National Park in Jamaica over 24 to 40 years coincided with invasion by a non-native tree, Pittosporum undulatum . By 2014, P. undulatum comprised, on average, 11.9% of stems ≥ 3 cm diameter and 10.4% of the basal area across 16 widespread plots within c. 250 ha of the forests. Across these plots, the more P. undulatum increased in basal area over 24 years, the greater the decline in local, plot-scale tree species richness, and the greater the reduction in the percentage of stems of endemic tree species. Plot-scale tree diversity (Shannon and Fisher's alpha) also declined the more P. undulatum basal area increased, but beta diversity across the plots was not reduced. Declines in local-scale tree species diversity and richness as the invasion progresses is especially concerning because Jamaica is a global biodiversity hotspot. Native birds disperse P. undulatum seeds widely, and future hurricanes will probably further increase its invasion by reducing canopy cover and therefore promoting growth rates of its established shade-tolerant seedlings. Remedial action is needed now to identify forest communities with greatest endemism, and to protect them through a continuing programme of control and removal of P. undulatum . Highlights: A non-native tree, Pittosporum undulatum, is invading Jamaican montane rain forests. Its invasion accelerated after an intense hurricane in 1988 and has not slowed since. Local-scale tree species richness and diversity declines the more it invades. The percentage of stems of trees endemic to Jamaica declines the more it invades. A programme of control and removal is needed now to prevent further declines.